Normalcy, Bio-Politics and Disability: Some Remarks on the German Disability Discourse - Anne Waldschmidt (Disability Studies Quarterly, 2006)
In Germany the perspectives of disabled people have a special weight in the public discourse on new genetics. This paper concentrates on the critique developed by activists of the disability rights movement. It focuses on the discourse's patterns and regularities which show a rough historical structure, and on the main and most influential arguments. As a first step, a theoretical framework is sketched. It draws on the work of French philosopher Michel Foucault as well as that of German literary scientist Jürgen Link. The concepts of "governmentality," "bio-power," and "normalism" help to understand that normalcy and eugenics are modern apparatuses of power/knowledge. In analyzing the discursive patterns of the German disability discourse on bioethics, in particular the "historical argument" and the "feminist argument," it can be shown that the disability rights discourse still considers power mainly as a disciplining, repressive force. The paper concludes with a plead for a renewal of the critique in order to better understand the bio-political matrix of neoliberal society which not only provides risk-oriented programs and policies, but also governs our subjective ways of thinking.